2015
DOI: 10.1097/mbc.0000000000000145
|View full text |Cite
|
Sign up to set email alerts
|

Lung cancer chemotherapy agents increase procoagulant activity via protein disulfide isomerase-dependent tissue factor decryption

Abstract: Lung cancer patients undergoing chemotherapy have an elevated risk for thrombosis. However, the mechanisms by which chemotherapy agents increase the risk for thrombosis remains unclear. The aim of this study was to determine the mechanism(s) by which lung cancer chemotherapy agents cisplatin, carboplatin, gemcitabine, and paclitaxel elicit increased tissue factor activity on endothelial cells, A549 cells, and monocytes. Tissue factor activity, tissue factor antigen, and phosphatidylserine exposure were measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 51 publications
2
33
0
1
Order By: Relevance
“…mechanism, in addition to pleiotropic effects on normal vascular cells such as monocytes and endothelial cells [6][7][8][9], could thus contribute to the clinically well described cisplatin-induced hypercoagulability in GCT patients. In this regard, it is important to note that the presence of liver metastases was associated with an almost 5-fold increased risk for major thromboembolic events in GCT patients undergoing cisplatin-based combination chemotherapy [2], suggesting that direct effects of administered cytotoxic agents on cancer cells in gross tumor manifestations are likely to play a role in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…mechanism, in addition to pleiotropic effects on normal vascular cells such as monocytes and endothelial cells [6][7][8][9], could thus contribute to the clinically well described cisplatin-induced hypercoagulability in GCT patients. In this regard, it is important to note that the presence of liver metastases was associated with an almost 5-fold increased risk for major thromboembolic events in GCT patients undergoing cisplatin-based combination chemotherapy [2], suggesting that direct effects of administered cytotoxic agents on cancer cells in gross tumor manifestations are likely to play a role in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Most recently, protein disulfide isomerase (PDI) has been implicated in the activation of TF on cisplatin-treated NSCLC cells, an effect that was not associated with an increase in cellular TF antigen [8]. To investigate the role of PDI in our in vitro system, NT2 cells were co-incubated with cisplatin and either of two PDI inhibitors, bacitracin or rutin, for 48 hrs.…”
Section: Mechanisms Of Tf Pca Induction By Cisplatinmentioning
confidence: 99%
See 1 more Smart Citation
“…Isolated monocytes were re-suspended in RPMI-1640 supplemented with 10% heat-inactivated fetal bovine serum (FBS) and 100 U/ml penicillin-streptomycin at a density of 1 Â 10 6 cells/ml and treated with chemotherapy agents cisplatin, gemcitabine, carboplatin, and paclitaxel diluted in RPMI-1640 to 20, 60, 40, and 4 mmol/l, respectively, based on combinations and maximal plasma concentrations observed in cancer patients as previously reported [10].…”
Section: Isolation Of Human Peripheral Blood Monocytesmentioning
confidence: 99%
“…The procoagulant activity of cancer cells (pancreatic, breast, and colorectal) has been shown to be linked with the cell surface expression of tissue factor (TF) [8,9]. We have recently demonstrated that chemotherapy agents can induce procoagulant TF activity on the cell surface of lung cancer cells via TF decryption [10]. However, other potential mechanisms by which cancer and/or chemotherapy induce a hypercoagulable state include platelet activation [11], increasing levels of circulating TF and/or phosphatidylserine-bearing microparticles [12][13][14], and increasing levels of procoagulant cell-free DNA (CFDNA) [15].…”
Section: Introductionmentioning
confidence: 98%